KESELAMATAN KAPAL PENANGKAP IKAN, TINJAUAN DARI ASPEK REGULASI NASIONAL DAN INTERNASIONAL - Suwardjo, Djodjo; Haluan, John; Jaya, Indra; Poernomo, Soen'an H. (Jurnal Teknologi Perikanan dan Kelautan, 2017)
Fishing is a high risk occupation compared to other occupations. Charachteristics of the occupational in fishing vessel are dangerous, dirty and difficult, known as “3d”. Generally, fishing vessels size is relatively small size, majority under 24 m length, sailing and fishing in bad weather with rough sea with unskilled crews, so that those factors can increase the fatality rate of the fishing vessel crews. Fishing vessel safety is a complex interactions among human factor (skipper and crew’s members), machines (fishing vessel and safety equipment) and environmental (weather and fisheries management). Fishing safety problems emerge when minimum one of those elements of human factor, machines or environment is misfucntion. The objectives of this research is to identify national and international safety regulations for fishing vessel and also relationship between fishing vessel and merchant vessel safety policies in Indonesia. Research was carried out from May 2008 – March 2009. Data was collected from any kind of source, such as Agency for Marine and Human Resource Development, Directorate General of Capture Fisheries, Tegal Coastal Fishing Port, Pekalongan Archipelago Fishing Port, Cilacap Ocean Fishing Port and Ministry of Communication. Fishing vessel safety policy basically is based on fishing vessel’s seaworthiness, watchkeeping/ship manning, safety equipment, and pollution prevention from the ship activities in national level as well as international level. Fishing vessel seaworthiness and watchkeeping/ship manning policies as a control function from the goverment to the parties involved in fishing activities to increase safety of crews, fishing vessel and sea environment from fishing vessel activities. Due to the characteristics of the working conditions on fishing vessel, more complex social environment of the fishermen and great number of fishermen in Indonesia, regulations on fishing vessel safety; watchkeeping/ship manning; works in fishing; education, training and certification of fishing vessel personnel; and fishing port, should be separated from the merchant ship safety regulations as international organizations did.